Experimental evaluation and theoretical prediction of CO2 & CH4 permeation in PSF/PDMS composite membrane under the influence of membrane swelling - Suleman, M.S. (Wiley-Liss Inc., 2018)
A PSF/PDMS composite membrane was developed by film casting of polydimethylsiloxane (PDMS) over polysulphone (PSF) support. The CO2/CH4 separation performance of membranes was evaluated under dry and wet conditions to evaluate the influence of water swelling on the separation performance of the developed membrane. Gas permeance in developed pure and composite membranes was theoretically predicted considering the effect of swelling on gas permeation in the membrane. Swelling in the membrane was confirmed by comparing the cross-sectional morphology of the developed membranes before and after wet tests. Water swelling in the membrane affected the separation performance of PSF, and CO2 permeance decreased from 48.79 to 2.37 GPU at 1000 kPa. However, the PSF/PDMS composite membrane resisted the effect of water swelling, and CO2 permeance increased from 39.9 to 40.87 GPU at 1000 kPa. CO2 and CH4 permeation were fitted with the dual mode model to predict the permeation in developed membranes theoretically. Permeation under wet feed conditions was not well-explained by the existing dual mode model. Thus, a modified dual mode model was presented with the best prediction of gas permeation under the effect of water swelling in the membrane. Â© 2017 Canadian Society for Chemical Engineering